Transformation of Carbon Dioxide Into Linear Carbonates and Methane over Cu-ni and Ru-fe Supported on Pellets Activated Carbon (2023)
Carbon dioxide (an abundant, inexpensive, and renewable carbon resource) is one of the most significant greenhouse gases that cause global warming and climate changes. Carbon dioxide can be used to synthesize useful chemical products such as linear.